Determination of waterflow velocity of River Gongola and its significance to communities in North-Eastern Nigeria - Wanah, B. B; Mbaya, L. A; Yoriyo, K. P; Mbiimbe, E. Y.; Fai, F. Y. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The velocities of waterflow of River Gongola were determined to provide information for sustainable management of its water resources. The study adopted manual Surface Float Method (SFM) in determining flow velocities. The result showed that average monthly velocities for the months of July to October were 1.27, 1.02, 0.87 and 1.12 m/s respectively. August and September had the fastest flows with 1.02 and 0.87 m/s. The highest average surface water levels were attained in July to October with values of 1.74, 2.14, 2.72 and 1.43 m. The lowest stages recorded were in March, April and December 2022 with values of 0.5, 0.56 and 0.6 m and in January and February 2023 with values of 0.57 and 0.5 m. Average annual velocity was 2.14 m/s while average annual stage was 1.11 m. Water levels deeper than 2 meters were recorded in July (19 days), August (23 days) and September (11 days) giving a total of 53 days over an average channel bed of 173.46 m wide. The high velocities and stages of water levels in the four months is significantly high enough to support sustainable supply of water for use in agriculture domestic and industrial purposes for communities living downstream of the gauging station. It is recommended that policies be formulated on transferring the water to North Eastern Nigeria to mitigate the acute water scarcity in the Sahelian region and to recharge Lake Chad to augment the volume of water in the lake which is fast drying up due to climate change.